Dari ide ke proposal: Pelatihan menulis proposal penelitian secara mudah, tepat dan sistematis - Riantisari, Rahmawati; Nurrokhmini, Alfiati; Al Ghazali, Buya; Basuki, Basuki; Saniyah, Chomariyatun; Olivia, Dea Syifa (Nur Science Institute, 2025)
This community service activity was conducted in response to the low level of students' ability at the Faculty of Social Sciences and Humanities to write research proposals in accordance with academic standards. The main problems encountered include difficulties in formulating research problems, developing a systematic research background, selecting appropriate research titles, and understanding the format and structure of research proposals. The objective of this activity was to improve students' understanding and skills in writing well-structured, logical, and academically sound research proposals. The method employed was an interactive workshop that combined theoretical explanations and hands-on practice, including training in problem formulation using the 5W+1H approach, background writing grounded in theory and data, strategies for selecting relevant research titles, and a comprehensive understanding of the research proposal structure. The results indicate a significant improvement in participants' understanding and ability to develop the main components of a research proposal, as demonstrated by the preparation of individual proposal drafts. Furthermore, the high level of participants' enthusiasm and engagement throughout the activity suggests that the training method was effective and aligned with students' needs.